Radicalism and Terrorism in the 21st Century Implications for Security - Sroka, Anna; Castro-Rial Garrone, Fanny; Torres Kumbrián, Rubén Darío (Studies in Politics, Security and Society, 2016)
This book addresses the issues of radicalism and terrorism, which are of exceptional importance and relevance in contemporary society. Each of the two phenomena are analyzed from a multidisciplinary perspective. The book contains articles which explore legal, political, psychological, economic and social aspects of radicalism and terrorism. A portion of the contributions are of a theoretical nature, they constitute an attempt at constructing analytical frameworks for studies on the two phenomena. There are also studies of particular cases, such as radicalism in Poland and in Spain, as well as within the European Union as a whole. This collective work is a response to the need for analyses of two issues which are increasingly responsible for determining the level of security which characterizes the contemporary world.